2022
DOI: 10.1259/bjr.20210979
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of a commercially available deep-learning algorithm in supine chest radiographs following trauma

Abstract: Objectives : Trauma chest radiographs may contain subtle and time-critical pathology. Artificial intelligence (AI) may aid in accurate reporting, timely identification and worklist prioritisation. However, few AI programs have been externally validated. This study aimed to evaluate the performance of a commercially available deep convolutional neural network - Annalise CXR V1.2 (Annalise.ai)- for detection of traumatic injuries on supine chest radiographs. Methods: Chest radiographs with a CT performed within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Increased availability of CT scanning and clinical and artificial intelligence tools that can assess radiology images in real-time has the potential to further reduce times to clearance of cervical spines. 26,27 Efforts to translate this evidence to practice should consider the limitations of remote assessment and the present study. Patients in the present study were within a hospital environment where the mechanism of injury was low falls.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Increased availability of CT scanning and clinical and artificial intelligence tools that can assess radiology images in real-time has the potential to further reduce times to clearance of cervical spines. 26,27 Efforts to translate this evidence to practice should consider the limitations of remote assessment and the present study. Patients in the present study were within a hospital environment where the mechanism of injury was low falls.…”
Section: Discussionmentioning
confidence: 86%
“…The primary contributors to delays in clearance are the availability of a CT scan, particularly overnight and reporting of the scan. Increased availability of CT scanning and clinical and artificial intelligence tools that can assess radiology images in real‐time has the potential to further reduce times to clearance of cervical spines 26,27 …”
Section: Discussionmentioning
confidence: 99%
“…Among the 63 studies, 56 studies identified pneumothorax on chest radiography [ 26 81 ], four studies on computed tomography [ 82 85 ], one study on ECG [ 86 ], one study used chest radiography and photography using a smartphone [ 87 ], and one study used chest radiography and tabular data [ 88 ]. Six studies developed and internally tuned DLs [ 37 , 52 , 63 , 67 , 74 , 76 ], 25 studies also internally tested their DLs [ 32 , 33 , 35 , 38 , 40 , 41 , 43 , 45 , 47 , 48 , 50 , 55 , 60 , 65 , 69 , 70 , 73 , 75 , 79 83 , 85 , 86 ] and 32 studies externally tested the DLs [ 26 31 , 34 , 36 , 39 , 42 , 44 , 46 , 49 , 51 , 53 , 54 , 56 59 , 61 , 62 , 64 , 66 , 68 , 71 , 72 , 77 , 78 , 84 , 87 , 88 ].…”
Section: Resultsmentioning
confidence: 99%
“…In studies that performed external model validation, the median dataset size was 1137 (range 175–112 120). 17 studies included localisation of pneumothorax in model output to improve end-user interpretability [ 26 28 , 30 33 , 36 38 , 40 , 47 , 56 , 59 , 68 , 84 , 85 ]. Detailed DL characteristics are shown in supplementary table S3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation